Peranan Jasa Raharja Dalam Penggelolaan Lalu Lintas Dikota Batam - Betty Krisdayanti; Timbul Dompak (Prodi Ilmu Administrasi Negara, 2023)
The importance of transportation in contributing to the nation's financial development is enormous. The creation of problems in areas like auto crashes is only one example of how advancements mix science and science innovation, particularly in the sphere of transportation and traffic, may have both beneficial and negative effects on how people live their lives. The public authority grants protection benefits to victims of vehicle accidents by Law 34 on Traffic Accidents of 1964 Store, and in this execution, that responsibility is transferred to Jasa Raharja PT (Persero). Obligations and obligations are to gather assets from general society through gifts necessary engine vehicle proprietors are played out every year, and from there on is directed back to the local area through the protection remuneration to the person in question or the person in question's beneficiaries, which expect to lessen the weight of expenses because of street car crashes, which granted the amount of pay stipulated in the Traffic Accident Fund Rules of the Finance Minister Decree No. 36/PMK.010/2008, Great Benefit and Payment Obligatory